NOMINATIVE FIELD OF THE CONCEPT HAPPINESS IN LATIN - Pankiv, Uliana (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
The article is dedicated to the analysis of nominative field of the linguo-cultural concept Happiness in the Latin language. A corpus of its verbalizers which includes a variety of linguistic means, namely direct nominations of the concept felicitas, beatitudo, beatitia, fortuna which are marked by high frequency of usage, the greatest generalization in terms of their semantics in direct meaning, are stylistically neutral and form the core of the nominative field has been formed. This corpus also includes synonyms fors, commoditas, prosperitas, res secundae, res prosperae; common root words (units of different parts of speech) derivationally related to the main lexical means of verbalizing the concept (adjectives felix, beatus, beatificus, fortunatus, faustus, secundus, prosper, prosperus; verbs beare, fortunare, prosperare; adverbs feliciter, beate, fortunatim, fortunate). For the purposes of the study representative information of explanatory, etymological, bilingual translated and synonym lexicographic sources of the Latin language was used. Their dictionary definitions do not only verbalize the knowledge of antique people, but also help to shape a complete linguistic picture of the world of the ancient Romans. Traditionally for the methods of linguo-cultural research for the interpretation of the Latin lexemes-verbalizers of the concept Happiness a number of micro-contexts and paremic illustrations that clearly testify their semantic content which often goes beyond dictionary definitions, involves the components of moral-ethical and mental backgrounds since language does not only reflect reality but also interprets it was given.